The Role of the Mosque in Nurturing the Morality of Muslim Youth in Medan City: Perspectives of Youth, Imams, and Parents - Mawar Agustin Nasution (Yayasan Bayt Shufiya Nusantara, 2026)
This study examines the function of the mosque as a space for nurturing the morality of Muslim youth. It employs a qualitative field research approach conducted among the youth community of Abidin Mosque in Medan City. Data were collected through in-depth interviews, observation, and documentation involving key informants consisting of mosque youth, parents, and members of the Mosque Welfare Board (Badan Kesejahteraan Masjid/BKM). The data were analyzed descriptively and analytically through the stages of data reduction, data presentation, and conclusion drawing. The findings show that pengajian, or Islamic study gatherings, serve as the main medium for youth moral formation through the teaching of fiqh, aqidah, and religious values that become the foundation of ethical conduct. This process is reinforced through role modelling, worship practices, and social habituation, which foster respect, tolerance, and moral responsibility in young people's daily lives. The study also finds that youth moral formation in the mosque takes place integratively through the involvement of mosque administrators, parents, and the wider social environment, although it faces obstacles such as limited family and parental support. This article argues for a more strategic role of the mosque in shaping the morality of Muslim youth, while also underscoring the importance of understanding the mosque's place in the lives of contemporary Muslim young people.